Clinical Psychology / Science, Practice, and Culture - Pomerantz Andrew M (Sage Publications, 2008)
This text covers all subfields of clinical psychology thoroughly, including the history and current state of the field, clinical assessment, psychotherapy, ethical and professional issues, and specialized topics such as forensic and health psychology. Preface, Acknowledgements, Introducing Clinical Psychology, Defining Clinical Psychology, Evolution of Clinical Psychology, Current Controversies in Clinical Psychology, Cultural Issues in Clinical Psychology, Ethical Issues in Clinical Psychology, Conducting Research in Clinical Psychology, Assessment, Diagnosis and Classification Issues, The Clinical Interview, Intellectual and Neuropsychological Assessment, Personality Assessment and Behavioral Assessment, Psychotherapy, General Issues in Psychotherapy, Psychodynamic Psychotherapy, Humanistic Psychotherapy, Behavioral Psychotherapy, Cognitive Psychotherapy, Group and Family Therapy, Special Topics, Clinical Child and Adolescent Psychology, Health Psychology, Forensic Psychology, Glossary, References, Index.